Explaining the Causal Relationships Between Attachment Styles and Pain in Women with Rheumatoid Arthritis: The Mediating Role of Mood Disorders - Mardan, Fahimeh; Ghodsi, Parvaneh; Keykhosrovani, Moloud; Amini, Naser; Leilabadi, Leida (Journal of Assessment and Research in Applied Counseling (JARAC), 2025)
Objective: The present study aimed to explain the causal relationships between attachment styles and pain, with the mediating role of mood disorders in women with rheumatoid arthritis. Methods and Materials: In a cross-sectional study using structural equation modeling, 286 participants diagnosed with rheumatoid arthritis were selected through purposive sampling during the period from November 2022 to June 2023. The participants were recruited from three hospitals in Tehran: Loghman, Taleghani, and Shahid Tajrish. After obtaining informed consent and confirming the eligibility criteria, the participants entered the study process. Three indices—attachment styles, pain, and mood disorders—were completed by the participants at a single time point. Data were analyzed using SPSS and AMOS version 25 software. Findings: The data analysis showed that the path coefficient between mood disorders and pain was positive and significant (β = 0.291, p = 0.001). The indirect path coefficient between anxious attachment style (β = 0.045, p = 0.023) and avoidant attachment style (β = 0.111, p = 0.001) with pain was positive, while the indirect path coefficient between secure attachment style (β = -0.066, p = 0.001) and pain was negative and significant. Conclusion: The findings of this study, consistent with prior research, indicate a relationship between attachment styles and pain, mediated by mood disorders. Overall, mood disorders and attachment styles are crucial variables in understanding the pain experience in patients with rheumatoid arthritis, and they may serve as unique therapeutic targets in the multifaceted management of such conditions.